Making Steel: Understanding the Lived Experience - Beaton, Elizabeth (Scientia Canadensis, 1991)
ABSTRACTThis article describes the nature of the 'Steel Project' being undertaken by the Beaton Institute in Cape Breton. Using a phenomenological approach, researchers attempt to understand the nature of steelmaking technology and workers' particular part in it through interviews and other documentation. Examples of this approach are provided.